2017
DOI: 10.21470/1678-9741-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Depression, Anxiety and Coping Strategies after Heart Transplantation

Abstract: IntroductionHeart transplantation is the therapeutic procedure indicated to increase the survival of patients with refractory heart failure. Improvement in overall functioning and quality of life are expected factors in the postoperative period.ObjectiveTo identify and evaluate mental disorders and symptoms, such as depression and anxiety, quality of life and coping strategies in the post-surgical situation of heart transplantation.MethodsA cross-sectional, quantitative study with patients who have undergone h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
20

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 15 publications
2
28
1
20
Order By: Relevance
“…Depression is a disorder that induces severe social and economic problems in the modern society. Its pathogenesis has been well documented in the previous studies [1] and has been confirmed to be associated with repeated exposure to harmful stress, which may include a variety of social and un-social stimuli, such as poor parental care [2], drug addiction [3], and heart surgery [4]. The presently available antidepressants in clinic, such as the selective monoamine oxidase inhibitors and the serotonin reuptake inhibitors, ameliorate depressive symptoms mainly through rectifying the monoamine dysfunction in the brain [5][6][7].…”
Section: Introductionmentioning
confidence: 94%
“…Depression is a disorder that induces severe social and economic problems in the modern society. Its pathogenesis has been well documented in the previous studies [1] and has been confirmed to be associated with repeated exposure to harmful stress, which may include a variety of social and un-social stimuli, such as poor parental care [2], drug addiction [3], and heart surgery [4]. The presently available antidepressants in clinic, such as the selective monoamine oxidase inhibitors and the serotonin reuptake inhibitors, ameliorate depressive symptoms mainly through rectifying the monoamine dysfunction in the brain [5][6][7].…”
Section: Introductionmentioning
confidence: 94%
“…Пациенты после пересадки сердца используют разные виды защитных механизмов, и более активное применение защитных механизмов приводит к психологической подготовленности к трансплантации [4,5]. Уровни качества жизни (КЖ) в сфере физического благополучия у больных после ТС улучшаются, результаты лучше у физически активных пациентов [6].…”
Section: Discussionunclassified
“…While data from several groups, including our own, have suggested that elevated depressive symptoms occurring in the first year post‐transplant are associated with greater risk of long‐term rejection and mortality, this is the first study to demonstrate it is independent of objectively assessed PA. QoL is increasingly recognized as an important marker of “transplant success”, with some transplant recipients prioritizing QoL as comparably important to clinical outcomes . Surprisingly, psychological QoL indices do not necessarily improve after transplant and may actually worsen over time and may differ by transplant group . Although few studies have examined PA correlates of QoL following transplant, prospective studies among heart transplant recipients suggest that changes in functional capacity do not associate with QoL changes …”
Section: Discussionmentioning
confidence: 99%